RANCANG BANGUN PURWARUPA TEKNOLOGI MIKROHIDRO MENGGUNAKAN KONSEP HIDRO FLUTTER - I P G Sopan Rahtika; I Made Suarta; Putu Wijaya Sunu (Politeknik Negeri Batam, 2019)
The decline of the world oil reserves is a global crisis for decades to come. The search for renewable energy alternatives is an urgent topic of current research trends. Indonesia has an abundance of energy availability in the form of potential microhydro development. This research is a research of development of new innovative technology in microhydro technology in the form of conversion technique of water flow energy into electric energy using hydro flutter technology. In this research, the development of new tool to convert energy from water flow into electrical energy was developed. A prototype was built that can extract energy from the water stream at times into mechanical energy ready for conversion into electrical energy using the hydro flutter principle of a flexibly mounted free leading edge cantilevered rigid plate. The advantages of the new concept are the simplicity of the design and the ability to clean the system by itself, thereby reducing the maintenance costs.